Implementation of Sambang by Bhabinkamtibmas for Pressing the Numbers of Motor Vehicle Theft in Jurisdiction of Karawang Police Resort - Dwitiya, Bunga Herlin; Setyabudi, Chairul Muriman; Nita, Surya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research was motivated by the theft of motor vehicles in the Karawang regency in the last five years to the crime of the highest with the number 176 cases in 2019 Bhabinkamtibmas as the police officer in the village has a preventive role with sambang to suppress motor vehicle theft in Karawang Regency, especially Klari District. The purpose of this study was to determine the implementation of sambang by Bhabinkamtibmas and what factors were inhibiting it, as well as innovations in suppressing the number of thefts. As a knife of analysis in this study, using management theory, the concept of Bhabinkamtibmas, the concept of sambang, and the concept of implementation. This research was conducted with a qualitative approach, using the type of field research, as well as interview data collection techniques, observations, and document review. From the results of the study, the authors found several facts that we're still unfulfilled, namely, they did not have data on the community of their fostered village, there was no recidivist data regarding the perpetrators of theft, did not have the name cards of Bhabinkamtibmas members, there was no inspection of the tidiness of the body and officers' equipment and messages that were sent. Conveyed that it has not been directed towards theft of motorized vehicles, not all members of Bhabinkamtibmas have attended vocational education. It can be concluded that there are still many shortcomings that are found, for that the author provides input to hold night patrols to maintain security, especially at vulnerable hours, and provide Bhabinkamtibmas vocational education. Approaching individuals who have dealt with the police so that they are not antipathetic to Bhabinkamtibmas, giving rewards so that Bhabinkamtibmas is maximal in carrying out its duties, and making innovations to reduce the number of vehicle theft crimes by developing media for delivering Bhabinkamtibmas messages through Instagram, Facebook, Twitter or YouTube to make it more interesting.